The Effectiveness of Madrasah Head Supervision in Student Counseling Guidance at MAN Insan Cendekia Bengkulu Tengah - Wulandari, Lisa; Evalia, Roza; Distiana, Tisa (Al-Khair Journal: Management Education, 2025)
Abstract: Supervision by the madrasa principal in guidance and counseling (BK) services across various educational units is still not running optimally due to time limitations, minimal coordination, and students’ low understanding of Guidance and Counseling. This study aims to analyze the effectiveness of the madrasa principal’s supervision in student Guidance and Counseling at MAN Insan Cendekia Bengkulu Tengah. It employs a descriptive qualitative method. Data sources were obtained through observation, interviews, and documentation, with data analysis based on the Miles and Huberman model. The results of the study indicate that the supervision of the madrasa principal, which includes planning, implementation, and evaluation, has been carried out quite effectively, supported by orderly administration and Guidance and Counseling services that align with students’ needs. Guidance and Counseling services in the madrasa cover personal, social, academic, and career aspects, with program implementation that is structured through regular assessments and continuous follow-up actions. The supervision has also strengthened coordination among the madrasa principal, Guidance and Counseling teachers, and other school stakeholders, thereby supporting the improvement of the quality of Guidance and Counseling services. Therefore, it can be concluded that the supervision of the madrasah principal has been running effectively in providing guidance and counseling services for students, although several obstacles such as limited time, workload, and supporting facilities still require attention to improve the effectiveness of services on an ongoing basis. Thus, it is recommended to enhance the effectiveness of the madrasah principal’s supervision in student guidance and counseling at the madrasah.Keywords: Effectiveness, Principal’s Supervision, Student Guidance and Counseling. Abstrak: Supervisi kepala madrasah dalam layanan bimbingan konseling (BK) di berbagai satuan pendidikan, masih belum berjalan optimal akibat keterbatasan waktu, minimnya koordinasi, serta rendahnya pemahaman peserta didik terhadap Bimbingan Konseling. Penelitian ini bertujuan untuk menganalisis efektivitas supervisi kepala madrasah dalam Bimbingan Konseling peserta didik di MAN Insan Cendekia Bengkulu Tengah. Menggunakan metode kualitatif deskriptif. Sumber data melalui observasi, wawancara, dan dokumentasi dengan analisis data model Miles dan Huberman. Hasil penelitian menunjukkan bahwa supervisi kepala madrasah mencakup perencanaan, pelaksanaan, dan evaluasi telah berjalan cukup efektif, kerapian administrasi, serta layanan Bimbingan Konseling sesuai kebutuhan peserta didik. Layanan BK di madrasah telah meliputi aspek pribadi, sosial, belajar, dan karier dengan pelaksanaan program yang terstruktur melalui asesmen berkala dan tindak lanjut yang berkesinambungan. Supervisi juga telah memperkuat koordinasi antara kepala madrasah, Guru Bimbingan Konseling, dan unsur sekolah lainnya sehingga mendukung peningkatan kualitas layanan Bimbingan Konseling. Oleh karena itu, dapat disimmpulkan bahwa supervisi kepala madrasah telah berjalan efektif dalam melayani bimbingan konseling peserta didik, meskipun beberapa kendala seperti keterbatasan waktu, beban kerja, dan sarana pendukung masih memerlukan perhatian untuk meningkatkan efektivitas layanan secara berkelanjutan. Sehingga dapat disarankan untuk tingkatkan efektifitas supervisi kepala madrasah dalam bimbingan konseling peserta didik di madrasah.Kata kunci: Efektivitas, Supervisi Kepala Madrasah, Bimbingan Konseling Peserta Didik.